WOMEN’S AUTONOMY AND RESPECTFUL CARE IN THE MATERNITY CARE DURING COVID-19 PANDEMIC - Rufidah Maulina; Safella Lutfatul Jannah; Gita Kostania; Revi Gama Hatta Novika; Niken Bayu Argaheni; Siska Ningtyas Prabasari (Indonesian Midwifery and Health Sciences Journal, 2023)
Background: Women's autonomy and respect are crucial for ensuring high-quality maternity care. However, during the COVID-19 pandemic, healthcare workers have had to adapt to new protocols and follow social distancing regulations, which can impact their ability to provide autonomous and respectful care to their patients. Therefore, the objective of this study was to describe how mothers perceive autonomy and respect during their antenatal and childbirth care. Method: This study used a cross-sectional approach to collect data via an online survey from March 2020 to July 2021. Descriptive statistics were used to analyze the data. Results: The majority of the women in this study reported experiencing a moderate level of autonomy (Mean ±SD=31.4±10.08) but low levels of respect during their maternity care (Mean ±SD= 44.99±7.13). Conclusion: The results of this study suggest that, during the COVID-19 pandemic, women are receiving moderate levels of autonomy in decision-making but low levels of respectful care from maternity staff during pregnancy and childbirth. Despite the challenges posed by the pandemic, healthcare workers such as midwives, nurses, and obstetricians should remain mindful of their patients' rights to make decisions about their own health and provide respectful care.